A self-* auction server: design principles, architecture and implementation. (16th December 2010) - Vilajosana, X.; Marques, J.M.; Juan, A.; Lazaro, D.; Krishnaswamy, R.; Navarro, L.
The use of economic models to handle resource allocation in the grid is a reality. Auction mechanisms are used in grid and distributed testbeds to elicitate user's preferences while improving the performance of the system. Existing implementations rely on single auction mechanisms to allocate resources whilst grids are heterogeneous in nature. Many different applications cohabitate having different workflow requirements such as bag of tasks executions or real time interaction that cannot be dealt efficiently by a single mechanism. In that scenario it would be more realistic to allocate resources using the most suitable mechanism for each situation, enabling also its configuration, deployment and management at runtime. Therefore, the paper presents the design principles, architecture and implementation of a configurable auction server (CAS). The auction server offers support for the deployment, configuration and execution of different auction mechanisms, facilitating the task of market mechanism developers and enabling the execution of distributed marketplaces according to local demand.